STUDI KUALITAS PELAYANAN KEPERAWATAN DI IGD RSUD JOMBANG - Pujiani, Pujiani; Mulyono, Mulyono (Universitas Pesantren Tinggi Darul Ulum, 2020)
Abstract Nursing services have an important role in the implementation of health services in hospitals. Services are all efforts made by employees to fulfill customer desires with services to be provided. The research objective was to describe the quality of nursing services in the Emergency Room. The design in this study used a descriptive description of the quality of service in the Emergency Room. The population is all families of patients in the Emergency Room . The variable in this study is the quality of nursing services. The sample in this study were part of the patient's family in the Emergency Room. The sample of this study is 67 respondents. The sampling technique in this study used purposive sampling. Data collection using instruments in the form of a questionnaire or questionnaire with a Likert scale. Before the questionnaire is used in the study, a trial is conducted to meet the valitidas and instrument reliability. The results showed that the assessment of the quality of nursing services that had been given to the respondents including reliability, responsiveness, emphathy, assurance, and tangible were mostly in good categories.Keywords: Quality of nursing services, Emergency Room, Nursing